Epidemia do vírus Zika e microcefalia no Brasil: Emergência, evoluç\~ao e enfrentamento - Leila Posenato Garcia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– In 2016, the causal relationship between Zika virus infection in pregnant women and the occurrence of microcephaly in infants was confirmed. However, in the previous year, when an unexpected increase in the number of live births with microcephaly was observed in Brazil, this relationship was unknown in the scientific literature. Timely and coordinated actions - with the participation of national and international health authorities, health workers and researchers - allowed the Zika virus to be proven to be implicated in the causality of a congenital syndrome and Guillain-Barré Syndrome (GBS) in a few months. This discussion paper aims to present a brief review of the history of the Zika virus epidemic and microcephaly in Brazil, from its emergence, through its evolution, to the policies and actions adopted to tackle it. Initially, the trajectory of the Zika virus in the world, from its discovery, in the Zika forest in Uganda, through its occurrence in Southeast Asia, until its emergence in Brazil is presented. Next, the process of declaring the microcephaly epidemic as a Public Health Emergency of National Concern (PHENC), by the Brazilian government, and Public Health Emergency of International Concern (PHEIC), by the World Health Organization (WHO), as well as the processes triggered by those measures. One topic is dedicated to describe the findings that contributed to the confirmation of the causal relationship between Zika virus infection and the occurrence of microcephaly, as well as GBS. In another topic, the evolution of the microcephaly epidemic in Brazil is described, highlighting the nine-fold increase in the number of cases in 2015 compared to the average of the previous five years, and the occurrence of the epidemic peak in the last quarter of this year. Following the main actions aimed at confronting the Zika virus epidemic in Brazil are presented. Finally, challenges for the prevention and control of the Zika virus and the consequences in the Brazilian epidemiological scenario are highlighted. The role of the Brazilian National Health System (SUS) in mobilizing all sectors necessary to confront the Zika virus epidemic is pointed and the need for resources for the continuity and improvement of the surveillance and control actions of arboviral diseases, as well as the attention to affected families, is highlighted.
Keywords: I12; 330; Zika virus infection; Zika virus; microcephaly; epidemics; international sanitary regulations; epidemiological surveillance; Brazilian National Health System; Pan American Health Organization; World Health Organization